Design of Capacity Development Program in Digital Mindset for Vocational Lecturers in Ministry of Transportation - Febrina, Rima; Mahmudi, Wahid (Kontigensi : Jurnal Ilmiah Manajemen, 2024)
The Ministry of Transportation holds 22 civil service schools divided into land, sea, air, and railway dimensions and has a role in producing reliable, professional, qualified transportation apparatus, with link and match in the labor market. Digital transformation not only forces government bureaucracy to change with the pattern of technology utilization, but also in learning method. Lecturers' digital skills play a role in aligning education patterns with the millennial generation and adapting with global standards. The results of the digital mindset competency mapping of Lecturers in the Ministry of Transportation found that 13% of Lecturers were still in the low competency category, 11% in the high category, and 73% in the intermediate category. Gap analysis was carried out using the TNA instrument method and recommendations for filling the competency gap through curriculum design and syllabus for Digital Mindset for Lecturer training. The program will have a strong focus on digitalization of teaching materials, artificial intelligence in the academic world, and Implementation of Technology in Scientific Work, Research, and Publication. The design of capacity development program including the supporting training program, micro-learning, and other competency development program based on Regulation of the State Administration Agency of the Republic of Indonesia Number 10/2018.